Evaluation of effectiveness of three cellulose derivative-based edible coatings on changes of physico-chemical characteristics of ‘Berangan’ banana (Musa sapientum cv. Berangan) during storage at ambient conditions - Malmiri, Hoda Jafarizadeh; Osman, Azizah; Tan, Chin Ping; Abdul Rahman, Russly (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Three edible coating formulations, namely methyl cellulose (MC)-glycerol, sodium carboxymethyl cellulose (Na-CMC) - glycerol and hydroxypropylmethyl cellulose (HPMC) - stearic acid-glycerol with three concentrations of main edible components, MC (2, 3.5 and 5% w/v), Na CMC (0.1, 0.8 and 1.5% w/v) and HPMC (2, 4 and 6% w/v) were applied on the peel surface of green mature Berangan banana and stored at 26±2°C and 40-50% relative humidity. Results showed that coated banana using high concentration (1.5% w/v) of Na-CMC and 1% (w/v) glycerol had the least weight loss, total colour difference and total soluble solids content (7.14%, 6.06 and 3.95° Brix, respectively) and had the highest firmness and pH (20.42 N and 5.36) at day 10 of storage while the control samples were already completely ripened. This was followed by banana coated with low concentrations of Na-CMC (0.1% w/v)-glycerol (1% w/v) and HPMC (2% w/v)-stearic acid (1% w/v)-glycerol (1% w/v), MC and control. However, no significant difference was observed between banana coated with low concentration of MC (2% w/v)-glycerol (1.25% w/v) and control.